Soil aggregation and associated organic carbon fractions as affected by tillage in a rice-wheat rotation in north India - Kumari, Mamta; Chakraborty, Debashis; Gathala, Mahesh K.; Pathak, H.; Dwivedi, B.S.; Tomar, Rakesh K.; Garg, R.N.; Singh, Ravender; Ladha, Jagdish K. (Wiley, 2011)
Soil samples were obtained from a long‐term trial conducted on a silty loam at Sardar Vallabhbhai Patel University of Agriculture and Technology, Modipuram (Meerut), in 2007–2008 to study the effects of various combinations of conventional and zero‐tillage (ZT) and raised‐bed systems on soil aggregation and associated organic C fractions in the 0‐ to 5‐cm and 5‐ to 10‐cm depth in a rice–wheat (Orysa sativa L.–Triticum aestivum L.) rotation. Macroaggregates increased under a ZT rice (direct‐seeded or transplanted) and wheat rotation with the 2‐ to 4‐mm fraction greater than that of the 0.25‐ to 2‐mm fraction. Bulk and aggregate associated C increased in ZT systems with greater accumulation in macroaggregates. The fine (0.053–0.25 mm) intra‐aggregate particulate organic C (iPOM‐C), in 0.25‐ to 2‐mm aggregates, was also higher in ZT than conventional tillage. A higher amount of macroaggregates along with greater accumulation of particulate organic C indicates the potential of ZT for improving soil C over the long‐term in rice‐wheat rotation.